Apoptosis in megakaryocytes: Safeguard and threat for thrombopoiesis - Yang, Shuo; Wang, Long; Wu, Yuesong; Wu, Anguo; Huang, Feihong; Tang, Xiaoqin; Kantawong, Fahsai; Anuchapreeda, Songyot; Qin, Dalian; Mei, Qibing; Chen, Jianping; Huang, Xinwu; et al. (Frontiers in Immunology, 2023)
Platelets, generated from precursor megakaryocytes (MKs), are central mediators of hemostasis and thrombosis. The process of thrombopoiesis is extremely complex, regulated by multiple factors, and related to many cellular events including apoptosis. However, the role of apoptosis in thrombopoiesis has been controversial for many years. Some researchers believe that apoptosis is an ally of thrombopoiesis and platelets production is apoptosis-dependent, while others have suggested that apoptosis is dispensable for steady-state thrombopoiesis, and is even inhibited during this process. In this review, we will focus on this conflict, discuss the relationship between megakaryocytopoiesis, thrombopoiesis and apoptosis. In addition, we also consider why such a vast number of studies draw opposite conclusions of the role of apoptosis in thrombopoiesis, and try to figure out the truth behind the mystery. This review provides new insights into the relationship between megakaryocytopoiesis, thrombopoiesis, and apoptosis and finds new clues for the possible pathological mechanisms of platelet disorders caused by abnormal apoptosis.